Security in South America : the role of states and regional organizations - Tavares, Rodrigo (Lynne Rienner Publishers, Inc., 2014)
"What types of threats and conflicts affect the countries of South America? What roles can and should states and regional organizations play in maintaining both traditional and human security in the region? Ranging from armed conflicts, terrorism, and the arms trade to political crises, drug trafficking, and environmental concerns, Rodrigo Tavares provides a comprehensive discussion of the issues and actors that affect South American security."--Publisher's description.